Faktor-faktor yang Mempengaruhi Ketepatan Waktu Clearance Kapal di Kantor Kesehatan Pelabuhan Kelas II Mataram Wilayah Kerja (Wilker) Lembar Tahun 2023 - Datu Kusumajati; Lalu Sulaiman; Lalu Abdul Khalik (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The Port Health Office (KKP) is a Technical Implementation Unit (UPT) within the Ministry of Health of the Republic of Indonesia which is responsible to the Director General of Disease Prevention and Control (P2P). The Port Health Office (KKP) has at least three scopes of work, namely preventing disease and health problems, managing airport/port environmental health.This research was conducted to determine the factors that influence the timeliness of ship clearance at the Mataram Class II Port Health Office in thesheet working area. The type of research used is analytical observational research using a cross sectional approach. Analytical surveys are surveys or research that explore how and why this health phenomenon occurs. Cross sectional is a method where the independent variable and the dependent variable are observed at the same time. The cross sectional approach aims to explain the factors that influence the timeliness of services for ship clearance at the Mataram Class II Port Health Office in the 2023 Working Area. Based on the results of statistical analysis, it was found that p value = 0.000 or less than (0.05) in factor on the timeliness of filling the sinkhole, then we get p value = 0.026 or less than (0.05) on the ship's sanitary condition factor. This means that these two factors have an influence on the timeliness of ship clearance at the Mataram Class II Port Health Office in the Sheet Work Area. The results of the logistic regression analysis show that the dominant factor is the timeliness of filling out the synchroplasty on the timeliness of services for ship clearance at the Mataram Class II Port Health Office in the Sheet Work Area. There is an influence between the timeliness of filling the sinkhole and the timeliness of ship clearance and there is an influence of the sanitary condition of the ship and the timeliness of ship clearance at the Mataram Class II Port Health Office, Working Area (Wilker) Sheet.